Absolute quantitation of major human tear proteins using multiple reaction monitoring (MRM)-based mass spectrometry - Hu, Weishan (2012)
The tear film covering the epithelial cells of the eye’s surface is crucial to the visual function. It contains three layers of aqueous, lipid and mucin. Proteins were found in the aqueous layer of the tear film. Many studies showed that the tear film is an accessible and useful source in studying ocular surface disorders and biomarker discovery. However, the ultra-small volume of tears poses challenges in its analysis. Mass spectrometry-based multiple reaction monitoring (MRM) is a tandem MS (MS/MS) scan mode which allows rapid, sensitive and specific quantitation of multiple analytes (multiplex) in highly complex sample matrix. In this study, stable isotope-labeled standard peptides and LC-MRM/MS were used to develop method for absolute quantitation of major human tear proteins. Triplicate Global Control (GC) tear samples were prepared to evaluate on the reproducibility of their peak area and retention time. Results showed consistency between the samples’ peak area and retention time with CV less than 20% and 1% respectively. The MRM method established from reproducible results was then applied to study tear samples from